Corrosion behaviour, metal release and biocompatibility of implant materials coated by TiO2-sol gel chemistry - Detsch, Rainer; et al. (Biomedizinische Technik, 2005)
Alloys based on titanium or cobalt have been used as implant materials for decades with good success. Because of their natural oxide layer these alloys reveal good corrosion behaviour. In contact with physiological solution metal release takes place, which can cause inflammation. Coatings can improve the corrosion behaviour. In this study Ti6Al4V and Co28Cr6Mo alloys, which are frequently used as implant materials, were tested. Polished discs of these alloys and polished discs, which were coated with TiO-layers by sol-gel chemistry, were compared regarding their corrosion behaviour and metal ion releasing. The releasing of Al, V, Ti, Co, Cr and Mo was quantified by ICP-MS analysis. The TiO-coating reduced the release of all ions except of the Al-ion. Both alloys showed a deviating kinetic of ion releasing. In addition, cell response (cell vitality, cell proliferation, endothelial marker CD31 and actin allocation) of osteoblasts and endothelial cells were investigated.
Keywords: In vitro cell test; Ion release; Ti6Al4V- and Co28Cr6Mo-alloys; TiO2-coating